1992
DOI: 10.3109/00365529209000096
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Amino Acid Metabolism in Hepatobiliary Disorders

Abstract: Sulfur amino acid metabolism was studied in patients with mild to severe forms of liver dysfunction and compared with that of healthy controls. Patients with mild liver dysfunction (for example, Gilbert's syndrome) had a normal sulfur amino acid metabolism. With increased inflammatory activity and cirrhosis (for example, chronic active hepatitis, alcohol-induced cirrhosis, and hepatic coma) a decreased ability to metabolize methionine (to cysteine, with cystathionine accumulation) and cysteine (to inorganic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…As discussed by Morgan et al [1982], and exemplified by the extensive data in their article, typical (but not invariant) changes are increased concentrations of tyrosine and/or phenylalanine together with increased methionine, and decreases in valine, isoleucine, and leucine. In more serious liver disease mean cystathionine is above normal in urine [Mårtensson et al, 1992] and in serum [Look et al, 2000; Medici et al, 2010], and mean tHcy is slightly raised [Medici et al, 2010].…”
Section: Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…As discussed by Morgan et al [1982], and exemplified by the extensive data in their article, typical (but not invariant) changes are increased concentrations of tyrosine and/or phenylalanine together with increased methionine, and decreases in valine, isoleucine, and leucine. In more serious liver disease mean cystathionine is above normal in urine [Mårtensson et al, 1992] and in serum [Look et al, 2000; Medici et al, 2010], and mean tHcy is slightly raised [Medici et al, 2010].…”
Section: Liver Diseasementioning
confidence: 99%
“…For GNMT , methionine synthase , BHMT , and CBS , mRNA concentrations were normal in only 4%, 0%, 11%, and 27%, respectively. Cystathionine gamma‐lyase activity may also be deficient [Mårtensson et al, 1992; Look et al, 2000; Medici et al, 2010]. Patients with severe loss of one type of mRNA tend to have severe losses of the other types [Avila et al, 2000], so that the abnormalities of sulfur amino acid metabolism in question may usually be explained by one‐or‐another combination of these enzyme activity deficiencies.…”
Section: Liver Diseasementioning
confidence: 99%
“… 21 It has been shown that patients with liver disease have low serum cysteine, taurine and GSH concentration. 22 , 23 Nearly half of the cysteine is converted to GSH, and rest of that is converted into taurine and participates in protein synthesis depending on the need of the cells. 24 …”
Section: Introductionmentioning
confidence: 99%
“… 11 It has been reported that patients with liver injury have a low serum concentration of taurine, cysteine, and GSH. 12 , 13 Most of the cysteine is used for GSH synthesis and some is used for taurine and protein synthesis depending on the need of the cells. 14 It could be suggested that lowering the rate of catabolism of cysteine to taurine could preserve the cysteine supply for GSH synthesis.…”
Section: Introductionmentioning
confidence: 99%